Discriminating dengue‐infected hepatic cells (WRL‐68) using dielectrophoresis. Issue 3 (2nd December 2015) - Yafouz, Bashar; Kadri, Nahrizul Adib; Rothan, Hussin A.; Yusof, Rohana; Ibrahim, Fatimah
Abstract : Dielectrophoresis (DEP), the induced movement of dielectric particles placed in a nonuniform electric field, has been used as a potential technique for manipulation and separation of many biological samples without destructive consequences to the cell. Cells of the same genotype in different physiological and pathological states have unique morphological and structural features, therefore, it is possible to differentiate between them using their DEP responses. This paper reports the experimental discrimination of normal and dengue‐infected human hepatic fetal epithelial cells (WRL‐68 cells) based on their DEP crossover frequency, at which no resultant movement occurs in the cells in response to the DEP force. A microarray dot electrode was used to conduct the DEP experiments. The DEP forces applied to the cells were quantified by analyzing the light intensity shift within the electrode's dot region based on the Cumulative Modal Intensity Shift image analysis technique. The differences in dielectric properties between infected and uninfected cells were exploited by plotting a unique DEP spectrum for each set of cells. We observed that the crossover frequency decreased from 220 kHz for the normal WRL‐68 cells to 140 kHz after infection with the dengue virus in a medium conductivity of 100 μS/cm. We conclude that the change in the DEP crossover frequency between dengue‐infected cells and their healthy counterparts should allow direct characterization of these cell types by exploiting their electrophysiological properties.